2014
DOI: 10.1037/lhb0000066
|View full text |Cite
|
Sign up to set email alerts
|

Do confessions taint perceptions of handwriting evidence? An empirical test of the forensic confirmation bias.

Abstract: Citing classic psychological research and a smattering of recent studies, Kassin, Dror, and Kukucka (2013) proposed the operation of a forensic confirmation bias, whereby preexisting expectations guide the evaluation of forensic evidence in a self-verifying manner. In a series of studies, we tested the hypothesis that knowing that a defendant had confessed would taint people's evaluations of handwriting evidence relative to those not so informed. In Study 1, participants who read a case summary in which the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 60 publications
(106 reference statements)
1
62
1
Order By: Relevance
“…Other research has shown that a strong belief in a suspect's guilt can also bias lay people's judgments of handwriting samples (Kukucka & Kassin, ), their willingness to vouch as an alibi for a confederate (Marion et al., ), their perceptions of whether degraded speech recordings contain incriminating remarks (Lange, Thomas, Dana, & Dawes, ), and the judgments of experts who are presented with inconclusive polygraph charts (Elaad, Ginton, & Ben‐Shakhar, ) and latent fingerprint samples (Dror & Charlton, ).…”
Section: The Consequences Of Confessionmentioning
confidence: 99%
“…Other research has shown that a strong belief in a suspect's guilt can also bias lay people's judgments of handwriting samples (Kukucka & Kassin, ), their willingness to vouch as an alibi for a confederate (Marion et al., ), their perceptions of whether degraded speech recordings contain incriminating remarks (Lange, Thomas, Dana, & Dawes, ), and the judgments of experts who are presented with inconclusive polygraph charts (Elaad, Ginton, & Ben‐Shakhar, ) and latent fingerprint samples (Dror & Charlton, ).…”
Section: The Consequences Of Confessionmentioning
confidence: 99%
“…As further testament to its power, recent work has identified ways in which a confession, once obtained, alters the course of a criminal case. For example, confessions can corrupt other evidence in ways that create illusory corroboration (e.g., Hasel & Kassin, ; Kukucka & Kassin, ) while also suppressing exculpatory evidence (Marion, Kukucka, Collins, Kassin, & Burke, ). At trial, confessors may be more likely to receive ineffective counsel (Kukucka & Kassin, ) and less likely to be granted post‐conviction appeals (Kassin, ) than other defendants.…”
Section: Discussionmentioning
confidence: 99%
“…As further testament to its power, recent work has identified ways in which a confession, once obtained, alters the course of a criminal case. For example, confessions can corrupt other evidence in ways that create illusory corroboration (e.g., Hasel & Kassin, 2009;Kukucka & Kassin, 2014) while also suppressing exculpatory evidence (Marion, Kukucka, Collins, Kassin, & Burke, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While patient selection bias is, in general, commonly acknowledged in the research community, confirmation bias can be more insidious . Confirmation bias is a type of selection bias that occurs when a particular reference standard is required for study inclusion.…”
mentioning
confidence: 99%